THE DEVELOPMENT OF TEACHING MATERIALS ON PRACTICE BASED- MAIL HANDLING INPROMOTING THE COMPETENCE OF OFFICE ADMINISTRATION SKILLS INBUSINESS AND MANAGEMENT AREA IN VOCATIONAL SCHOOLS - Indrawati, C. Dyah Sulistyaningrum (Dewantara, 2013)
Purpose:The aim of this study is to: (1) describe the teaching materials of handling mail currently used as the competency of Office Administration skill in Business and Management vocational school, (2) formulate the development of teaching materials prototype to be teaching materials of practicum/practice mail handling on the competency of office administration skill on busines and and Management, and  (3) determine the effectiveness level of teaching materials based on practice of competency skills in Office Administration) in some vocational schools in Surakarta and Karanganyar. Method:This research used 3 data collection techniques. There were : (1) a preliminary study by interview, observation and documentation, (2) limited testing and more extensive trials with interview techniques,  focus group Discusión (FGD), and test techniques, (3) the effectiveness test by IQ tests and practice tests, also attitude scales test. Analysis of data are : (1) A preliminary study with interactive analysis, (2) limited and extensive trials/tests with interactive analysis and anakova statistical analysis, (3) and effectiveness test with anakova statistical analysis. Findings: The research found that :  (1) limited test qualitatively, the inputs from both the subject, the expert of teaching materials, and stakeholders, statistically FoRes = 13.3033> Ft = 4.08 and it means that there is a significant difference in the learning achievement between the experimental group with the control group, (2) the anakova test without variabel of students covariate showedFoRes = 53.9957> Ft = 3.98, whereas anakova with covariates variable of students? learning motivation is FoRes = 48.7135 > Ft = 3.98.  It means that there are significant differences between the learning outcomes of experimental class  with the control class,  (3) from one way Anava test, IQ test shows FoRes = 3388 <Ft 4:06. It means that there are not IQ differences between the experimental and the control group. It is indicated that FoRes = 1336 <Ft 4:06.  It shows that there is not difference in students' attitudes toward mail handling subjects.Anakova without covariate variable of students learning motivation showed FoRes = 114 508> Ft = 3.92.  It means that there is a significant difference between learning outcomes without student motivation.   Anakova with covariates variable of students learning motivation is FoRes = 115 249> 3.92 Ft.  It shows that there is a significant difference between learning outcomes with student motivation. Keywords: Teaching Materials, Mail Handling, practice, modules